General View of Constitution Mall, Government Area and Theme Center, New York World's Fair 1939
Constitution Mall, leading from the Trylon and Perisphere to the Lagoon of the Nations, which just precedes the Government Area, is surrounded by many of the Fair's most impressive exhibit buildings. This beautiful esplanade is handsomely landscaped, contains lagoons, waterfalls and fountains, as well as many great statues.